ANALISA PENGATUR LENTURAN SISTEM MANUAL PADA SHOCK ABSORBER SEPEDA MOTOR: ANALYSIS OF MANUAL SYSTEM DEFLECTION CONTROLLER ON MOTORCYCLE SHOCK ABSORBER - Ghofur, Abdul (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
Comfort in the vehicle is needed, therefore the vehicle is equipped with a suspension system.The problem with the current suspension system is that the suspension system cannot be used according to the wishes of the rider, because it does not yet have a flexibility regulator that can be adjusted directly while driving. The purpose of this study, will make a device for adjusting the flexibility of the shock absorber electrically, so that the driver can adjust the flexibility of the shock absorber when the vehicle is running without having to stop. The results of this study shock absorber with a passenger load of 90.5 kg produces the largest bending length of 5.17 cm at a hole area of 28.26 mm². For a passenger load of 141.5 kg, the greatest flexibility is 7.06 cm. with a hole area of 28.26mm²